1972
DOI: 10.1021/i260043a004
|View full text |Cite
|
Sign up to set email alerts
|

Design of Cross-Flow Cooling Towers and Ammonia Stripping Towers

Abstract: nonrejecting (such as Eastman HT-00 used in this study on which dynamic membranes can be formed from sewage constituents) may find a place in treatment of sewage plant effluents where incomplete salt rejection can be tolerated and where substantially greater removal of turbidity and organic carbon is desired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The arsine, hydrogen selenide, and ammonia gas cylinders were installed in a safety chamber that vents into the safety hood. A face mask with a regulator specific for NH 3 and HCl, and personal protection monitors were obtained for use .The inlet gas flow rates were calculated for a desired composition in the feed gas and, once verified by bubble meter measurements, were maintained during experimentation by the rotameters, designated as (3), (6) and (9) in the Figure 9. The exit gas stream passed through a wash bottle containing sodium hydroxide (caustic -NaOH) for excess H 2 S removal after the trace metals were collected in inlet or outlet sample trains.…”
Section: Figure 7 Schematic Of Gti Vapor-liquid Equilibrium Cellmentioning
confidence: 99%
“…The arsine, hydrogen selenide, and ammonia gas cylinders were installed in a safety chamber that vents into the safety hood. A face mask with a regulator specific for NH 3 and HCl, and personal protection monitors were obtained for use .The inlet gas flow rates were calculated for a desired composition in the feed gas and, once verified by bubble meter measurements, were maintained during experimentation by the rotameters, designated as (3), (6) and (9) in the Figure 9. The exit gas stream passed through a wash bottle containing sodium hydroxide (caustic -NaOH) for excess H 2 S removal after the trace metals were collected in inlet or outlet sample trains.…”
Section: Figure 7 Schematic Of Gti Vapor-liquid Equilibrium Cellmentioning
confidence: 99%
“…The mean driving force was assumed to be the entering potential difference. Wnek and Snow (1972) present a practical design method for two applications: cooling tower, and ammonia stripping towers with simultaneous cooling. They observed that the temperature change of the liquid across the width of the tower is small in comparison to that across its height and this allows the development of an analytical solution of tower dimensions for stripping of ammonia from water.…”
mentioning
confidence: 99%